2018
DOI: 10.1007/s00280-018-3659-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of levetiracetam with phenytoin for the prevention of intravenous busulfan-induced seizures in hematopoietic cell transplantation recipients

Abstract: PurposeBusulfan is used as a conditioning regimen for hematopoietic stem cell transplantation and is known to cause seizures as a side effect. As various anticonvulsant drugs have been reported, we conducted a retrospective investigation regarding the preventive effects and adverse events associated with different anticonvulsants administered alongside intravenous busulfan (ivBu) in our institution.MethodsWe targeted 104 patients who received ivBu at our institution from May 1, 2010 to April 30, 2017. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…Busulfan-induced seizures were first reported in 1984 by Marcus et al 8 Studies have shown that busulfan-induced seizures occur at a frequency of 1-40% in patients without any anticonvulsant prophylaxis and breakthrough seizure rates of 0-15% in patients who are treated with prophylactic anticonvulsant therapy. 2,[9][10][11] The overall seizure prevention rate in our study was 98.5% therefore similar to the incidence reported throughout the literature. 1,7 Our results are in keeping with Akiyama et al, who found a seizure prevention rate of 98.6% with phenytoin and 100% for levetiracetam and concluded there was no difference in seizure breakthrough rate or adverse effects in an adult population.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Busulfan-induced seizures were first reported in 1984 by Marcus et al 8 Studies have shown that busulfan-induced seizures occur at a frequency of 1-40% in patients without any anticonvulsant prophylaxis and breakthrough seizure rates of 0-15% in patients who are treated with prophylactic anticonvulsant therapy. 2,[9][10][11] The overall seizure prevention rate in our study was 98.5% therefore similar to the incidence reported throughout the literature. 1,7 Our results are in keeping with Akiyama et al, who found a seizure prevention rate of 98.6% with phenytoin and 100% for levetiracetam and concluded there was no difference in seizure breakthrough rate or adverse effects in an adult population.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other studies comparing phenytoin and levetiracetam for busulfan seizure prophylaxis, we did not find any difference in the occurrence of oral mucositis any grade or veno‐occlusive disease 1,7,9 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations